Penggunaan Google Formulir pada Ujian Satuan Pendidikan Siswa Kelas XII SMA Azharyah Palembang - Mardiah, Leni (Journal of Innovation in Teaching and Instructional Media, 2021)
The aim of this study is to evaluate the impact of using Google Forms to assess Education Unit Exams, as well as student and teacher reactions to its use. This study employs a descriptive approach. Observation (observation), interview (interview), and documentation were used to collect data for this study. Data reduction, data display, and conclusion were all used in data analysis techniques. Students in class XII SMA Azharyah Palembang in the academic year 2020/2021 were the subjects of this research. According to the findings of this report, the use of Google Forms as a tool for evaluating the Education Unit Examination begins with the planning stages, the development of questions, the administration of exams, and the compilation of exam results. According to student responses, most students prefer using Google forms to evaluate educational unit exams because it saves time and allows exams to be completed anywhere. The use of Google Forms to enforce the Education Unit Examination will save the school money on operating costs including paper and office supplies, as well as make it easier to correct student answers.